Developing a Critical Reading Assessment Specification Infused with Ecological Literacy for Higher Education - Nurkhamidah, Neni; Lustyantie, Ninuk; Murtadho, Fathiaty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study addresses the limitations of existing critical reading assessments in Indonesian higher education, which often focus narrowly on comprehension and recall, neglecting higher-order critical thinking and ecological literacy skills essential for addressing complex environmental challenges. The problem is evident as students frequently achieve near-perfect scores on current tests that inadequately measure their ability to critically analyze academic texts or apply ecological awareness. This research develops a comprehensive assessment specification for a Critical Reading course at Media Nusantara University that integrates ecological literacy alongside traditional reading skills. Using a Design and Development Research (DDR) methodology, the study analyzed course syllabi, learning outcomes, and existing assessments, and incorporated feedback from a Focus Group Discussion (FGD) involving one lecturer and two assessment experts, alongside interviews with five students. The resulting assessment balances multiple-choice questions with open-ended essay tasks and includes ecological case studies to better evaluate higher-order thinking and real-world problem-solving abilities. The revised assessment specification uniquely combines critical reading with ecological literacy to prepare students for both academic success and responsible environmental citizenship. Findings indicate that this approach fosters deeper engagement with texts and environmental issues and offers a practical framework for more valid and reliable assessments in higher education.